Developing Lecture Modules Using a Problem-Based Learning Model with Local Cultural Nuances to Improve Reasoning Ability - Simanungkalit, Rick Hunter; Simarmata, Gayus; Saragih, Widya Safira (Gema Wiralodra, 2024)
One of the abilities that educators must pay attention to when learning mathematics is mathematical reasoning abilities. Various efforts have been made by teachers, researchers and educational practitioners to improve mathematical reasoning abilities, but in reality, reasoning abilities are still in the low category. The aim of this research is to develop a lecture module with a problem-based learning model with local cultural nuances to improve reasoning abilities. Learning packaged in local culture is one way to make it easier to understand mathematics.The method used in this research is the development method with the Thiagarajan 4-D development design The research results show that the module developed is valid, effective and practical and can improve mathematical reasoning abilities